2019
DOI: 10.4067/s0717-97072019000304523
|View full text |Cite
|
Sign up to set email alerts
|

Zidovudine: Structural Modifications and Their Impact on Biological Activities and Pharmacokinetic Properties

Abstract: Zidovudine was the first drug approved for the treatment of Acquired Immuno Deficiency Syndrome (AIDS). Its chemical name is azidothymidine (AZT). AZT use is associated with bone marrow toxicity. Shorter half-life and inability to penetrate the blood-brain barrier are the pharmacokinetic problems of this important drug molecule. Various modifications have been carried out in the structure of AZT. These include modification of hydroxyl and azido group, thymidine ring, preparation of phosphate and phosphonate de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…1 Some studies on structural modifications of zidovudine (AZT) have shown that the 5′-OH group can be modified with better antiviral potency, pharmacokinetic properties, and cytoprotective properties. 6 Therefore, it was envisaged that new approaches could be adopted for antiretroviral agents (ARAs) with antioxidants (AO) (Figure 1). In this Viewpoint, we primarily assume an approach to make ARA−AO conjugates and in silico calculations have shown an increase of log p values and molecular weight (critical factors for CNS penetration and distribution).…”
Section: Clinical Status Of Antiretroviral Agents In the Treatment Of...mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Some studies on structural modifications of zidovudine (AZT) have shown that the 5′-OH group can be modified with better antiviral potency, pharmacokinetic properties, and cytoprotective properties. 6 Therefore, it was envisaged that new approaches could be adopted for antiretroviral agents (ARAs) with antioxidants (AO) (Figure 1). In this Viewpoint, we primarily assume an approach to make ARA−AO conjugates and in silico calculations have shown an increase of log p values and molecular weight (critical factors for CNS penetration and distribution).…”
Section: Clinical Status Of Antiretroviral Agents In the Treatment Of...mentioning
confidence: 99%
“…Clinical studies have reported that antiretroviral therapy (ART) in HAND has limitations due to poor CNS penetration and hence a lower concentration is maintained in the CSF to inhibit the viral replication and is found to be not very effective . Some studies on structural modifications of zidovudine (AZT) have shown that the 5′-OH group can be modified with better antiviral potency, pharmacokinetic properties, and cytoprotective properties . Therefore, it was envisaged that new approaches could be adopted for antiretroviral agents (ARAs) with antioxidants (AO) (Figure ).…”
Section: Clinical Status Of Antiretroviral Agents In the Treatment Of...mentioning
confidence: 99%
“…An important trend in the chemotherapy field involves the study of nucleoside analogs and the analysis of their multiple antioxidant, antitumor, antimicrobial, and antiviral properties [ 34 , 35 , 36 , 37 ]. Azidothymidine (AZT), also known as zidovudine (ZDV), is a synthetic nucleoside analog of thymidine that was originally synthesized as an antitumor compound but gained notable prominence due to its inhibitory activity on reverse transcriptase, an essential enzyme for HIV replication [ 38 , 39 ]. Interestingly, current studies have revealed that AZT has also been described as an inhibitor of SARS-CoV-2 RNA-dependent RNA polymerase (RdRp) in vitro (kinetic test) [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%